2021
DOI: 10.12688/f1000research.73180.1
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Predictive Modelling of Student Performance

Abstract: Background - Many factors affect student performance such as the individual’s background, habits, absenteeism and social activities. Using these factors, corrective actions can be determined to improve their performance. This study looks into the effects of these factors in predicting student performance from a data mining approach. This study presents a data mining approach in identify significant factors and predict student performance, based on two datasets collected from two secondary schools in Portugal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…When exploring other studies where machine learning was used to explore absenteeism, we found a few examining the relationship between asthma and absenteeism (Lary et al, 2019) predictive modeling of student performance (Ng et al, 2021), and attendance autistic students (Jarbou et al, 2022). More is surely available, but these give a glimpse into many types of opportunities for exploration using this method.…”
Section: Machine Learningmentioning
confidence: 99%
“…When exploring other studies where machine learning was used to explore absenteeism, we found a few examining the relationship between asthma and absenteeism (Lary et al, 2019) predictive modeling of student performance (Ng et al, 2021), and attendance autistic students (Jarbou et al, 2022). More is surely available, but these give a glimpse into many types of opportunities for exploration using this method.…”
Section: Machine Learningmentioning
confidence: 99%
“…Recently, Ng et al [7] have proposed a data mining approach for identifying essential factors that affect student performance based on data from two secondary schools in Portugal. Several machine learning algorithms are used for classification: Support Vector Machine (SVM), NB, and Multilayer Perceptron (MLP).…”
Section: Related Workmentioning
confidence: 99%
“…Another study [7] used the same dataset with three classification models: SVM, NB, and MLP. The performance indicators were F1-Score, recall, accuracy, and precision.…”
Section: Related Workmentioning
confidence: 99%
“…When exploring other studies where machine learning was used to explore absenteeism, we found a few examining the relationship between asthma and absenteeism ( Lary et al, 2019 ) predictive modeling of student performance ( Ng et al, 2021 ), and attendance autistic students ( Jarbou et al, 2022 ). More is surely available, but these give a glimpse into many types of opportunities for exploration using this method.…”
Section: Literature Reviewmentioning
confidence: 99%